Comparative Transcriptome Analysis of Shewanella putrefaciens WS13 Biofilms Under Cold Stress - Yan, Jun; Yang, Zhijun; Xie, Jing (Frontiers in Cellular and Infection Microbiology, 2022)
Shewanella putrefaciens is a Gram-negative bacterium that can cause seafood spoilage under low-temperature conditions. The bacterium easily forms biofilms to enhance its survival in challenging environments. Our previous research revealed that the biofilm formed by S. putrefaciens WS13 under the low temperature (4 °C) has larger biomass and tighter structure than at an optimum growth temperature (30 °C). In this study, comparative transcriptome analysis was further performed to get insights into the global-level of gene expression in the biofilm formed by S. putrefaciens WS13 under the refrigerating and optimal temperatures using Illumina RNA-Sequencing technique. The results revealed that a total of 761 genes were differentially expressed, of which 497 were significantly up-regulated and 264 were significantly down-regulated (p<0.05). The qRT-PCR results of randomly selected differentially expressed genes (DEGs) confirmed the RNA sequencing results. Comparison of transcriptome data revealed 28 significantly changed metabolic pathways under the cold stress, including the down-regulated chemotaxis, and motility, and up-regulated tryptophan metabolism, histidine biosynthesis, and quorum sensing, which benefited the biofilm formation of S. putrefaciens WS13 under the adverse circumstance. This study provided useful data for better understanding of the biofilm formation of S. putrefaciens, and also laid a theoretical foundation for novel vaccine and drug targets against the severe spoilage bacterium under the cold stress.